2021
DOI: 10.3389/fimmu.2021.625165
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte Colony-Stimulating Factor Effectively Mobilizes TCR γδ and NK Cells Providing an Allograft Potentially Enhanced for the Graft-Versus-Leukemia Effect for Allogeneic Stem Cell Transplantation

Abstract: Allogeneic hematopoietic stem cell transplantation (HSCT) is a potential cure for patients with hematological malignancies but substantial risks of recurrence of the malignant disease remain. TCR γδ and NK cells are perceived as potent innate effector cells in HSCT and have been associated with post-transplant protection from relapse in clinical studies. Immunocompetent cells from the donor are crucial for patient outcomes and peripheral blood stem cells (PBSC) are being increasingly applied as graft source. G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…The outstanding question is at what point the NK cell maturational trajectory is interrupted in these patients. NK cell progenitors are functionally impaired in G-CSF mobilized stem cell products, albeit peripheral CD56 bright/dim ratios appear to be unaffected 55,56 . We found normal absolute numbers of CD56 bright with non-aberrant phenotypes, suggesting that the homeostatic defect is downstream of progenitor stages, primarily affecting the CD56 dim NK cell compartment.…”
Section: Discussionmentioning
confidence: 99%
“…The outstanding question is at what point the NK cell maturational trajectory is interrupted in these patients. NK cell progenitors are functionally impaired in G-CSF mobilized stem cell products, albeit peripheral CD56 bright/dim ratios appear to be unaffected 55,56 . We found normal absolute numbers of CD56 bright with non-aberrant phenotypes, suggesting that the homeostatic defect is downstream of progenitor stages, primarily affecting the CD56 dim NK cell compartment.…”
Section: Discussionmentioning
confidence: 99%
“…26 Furthermore, G-CSF may mobilize a high number of HLA-DR + TCR gamma-delta cells, increase the CD56dim subpopulation of NK cells, and upregulate the expression of the activating receptor NKG2D, all of which are associated with antitumor effects and peripheral tolerance. 11,12 A retrospective, single-center study reported that G-CSFprimed DLI improved the rate of conversion into full donor chimerism and reduced CIR without increasing the incidence of GVHD. 9 By contrast, other retrospective studies 27,28 and a metaanalysis involving 585 patients 29 have reported no significant difference between G-CSF-primed DLI and SS-DLI in terms of their effectiveness in preventing disease progression or GVHD development.…”
Section: Discussionmentioning
confidence: 99%
“…With the accumulation of clinical DLI experience and the changes in the relevant guidelines, 2009 onward, the policy for serial DLI shifted toward dose escalation. Considering the potential advantages of G-CSF-primed DLI indicated in several immunologic studies, 9,11,12 since 2017, we have been routinely cryopreserving an excessive amount of peripheral blood stem cell (PBSC) product obtained on day 0 of HSCT for future use in G-CSF-primed DLI. In studies focusing on SS-DLI, starting DLI doses ranging from 1 × 10 5 to 1 × 10 6 CD3 + cells/kg were used for prophylactic and preemptive purposes after matched sibling or unrelated donor HSCT and a higher initial dose (1 × 10 7 CD3 + cells/kg) was used for frank relapses.…”
Section: DLImentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, a more detailed analysis by Minculescu et al. showed that G-CSF preferentially mobilized naïve and terminally differentiated effector (TEMRA) γδ T cells over memory cells with a preferential increase in the non-Vδ2 subset while also increasing the proportion of HLA-DR expressing γδ T cells ( 67 ). Regarding the impact on TCR repertoire, it has been shown that G-CSF was associated with TCR repertoire disturbances in the form of alteration of distribution and clonality of some TRG and TRD subfamilies, suggesting a potential immune modulatory effect ( 70 ).…”
Section: Factors Affecting γδ T Cell Reconstitutionmentioning
confidence: 99%